Teaching to Impact Sexual Violence? The Evaluation of a Curricular Intervention for First-Year College Students. Issue 3 (March 2021) - Johnson, Katherine M.; Lederer, Alyssa M.; Liddell, Jessica L.; Sheffield, Sydney; McCraw, Alicia
Purpose: To evaluate whether a semester-long course for first-year undergraduates influenced knowledge, attitudes, and behavioral intentions about gender, sexuality, and sexual violence. Design: Quasi-experimental survey design. Setting: A private university in the Southeastern US. Participants: Undergraduates enrolled in an intervention (n = 49) or comparison (n = 60) course in Fall 2018. Measures: Sociosexual Orientation Inventory, Sexual Conservatism, Heteronormative Attitudes and Beliefs, Illinois Rape Myth Acceptance Scale, Bystander Efficacy Scale, Consent Myths, Sexual Misconduct Apathy, Campus Resource Awareness Index. Analysis: A 2-way mixed-factorial ANOVA. Results: Relative to the comparison group, students in the intervention course had significantly greater rates of change in reducing heteronormative views, decreasing sexual misconduct apathy, and increasing awareness of campus resources for sexual violence. Conclusion: A semester-long course targeting first-year undergraduates can potentially influence knowledge, attitudes, and behavioral intentions regarding sexual violence and create a more positive campus climate.